2013
DOI: 10.4161/rdis.24420
|View full text |Cite
|
Sign up to set email alerts
|

Yeast genetic screen reveals novel therapeutic strategy for ALS

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease caused by a selective loss of motor neurons. There is no cure and few effective treatments. The RNA-binding protein TDP-43 contributes to the pathogenesis of ALS. TDP-43 is depleted from the nucleus and accumulates in cytoplasmic aggregates in the degenerating neurons and glia of most ALS patients. Furthermore, mutations in the TDP-43 gene cause rare familial and sporadic forms of the disease. Thus, therapeutic strategies targeting TDP-43 may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 47 publications
(69 reference statements)
1
24
0
Order By: Relevance
“…Relevance and parallel of the yeast TDP-43-YFP expression model to ALS has been greatly supported by several cellular factors modulating the aggregation and toxicity in similar manner in both yeast and mammalian cell cultures304445. In fact, ataxin-2, a homolog of yeast PBP1 protein, was identified as an ALS risk factor after the role of PBP1 in modulating TDP-43 toxicity was deciphered in the yeast model3046. Therefore, owing to the relevance of the yeast TDP-43 aggregation model to ALS, we examined if the compound AIM4 also affects TDP-43 aggregation in the yeast cell.…”
Section: Resultsmentioning
confidence: 99%
“…Relevance and parallel of the yeast TDP-43-YFP expression model to ALS has been greatly supported by several cellular factors modulating the aggregation and toxicity in similar manner in both yeast and mammalian cell cultures304445. In fact, ataxin-2, a homolog of yeast PBP1 protein, was identified as an ALS risk factor after the role of PBP1 in modulating TDP-43 toxicity was deciphered in the yeast model3046. Therefore, owing to the relevance of the yeast TDP-43 aggregation model to ALS, we examined if the compound AIM4 also affects TDP-43 aggregation in the yeast cell.…”
Section: Resultsmentioning
confidence: 99%
“…Also, the extensive understanding of molecular mechanisms of yeast prion aggregation has further helped in using yeast as a model for human amyloid diseases (Wickner, ; Khurana and Lindquist, ; Liebman and Chernoff, ; Chernoff, ; Tuite et al ., ). As heterologous amyloid protein expression in yeast can lead to amyloid aggregation, large‐scale genetic and small molecule screens have been attempted for anti‐aggregation or anti‐toxicity of amyloid proteins from Alzheimer's, Huntington's and amyotrophic lateral sclerosis diseases (Manogaran et al ., ; Park et al ., ; Figley and Gitler, ).…”
Section: Introductionmentioning
confidence: 97%
“…Use of the yeast model revealed that several reported pathogenic mutations linked to ALS mapped to the C-terminus of TDP-43, which accelerated TDP-43 aggregation and decreased survival 27. These initial discoveries of TDP-43 disease biology have now been validated in various experimental models 928.…”
Section: Yeast Models Of Neurodegenerationmentioning
confidence: 99%
“…91011. As the core proteostasis machinery is remarkably well conserved across eukaryotes, yeast has emerged as a tractable organism to model proteostasis alterations in neural disease 141012.…”
Section: Introductionmentioning
confidence: 99%